-6j-19-11j=-20j+14

Simple and best practice solution for -6j-19-11j=-20j+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6j-19-11j=-20j+14 equation:



-6j-19-11j=-20j+14
We move all terms to the left:
-6j-19-11j-(-20j+14)=0
We add all the numbers together, and all the variables
-17j-(-20j+14)-19=0
We get rid of parentheses
-17j+20j-14-19=0
We add all the numbers together, and all the variables
3j-33=0
We move all terms containing j to the left, all other terms to the right
3j=33
j=33/3
j=11

See similar equations:

| 8r=-12+9r | | s–2+ 1=–2 | | 10.8n+5.17=6.84-5.9n | | s–2+1=–2 | | -16+v=19-4v | | -20-13y=-11y | | 9b=54b= | | 1000=1.2992x^2-114061x+3*10^9 | | 18-11w=-17-13w+9 | | 4c^2+7c+12c+21=0 | | -18.14+12.97+12.6r=13.8r+15.47 | | y/4+12=36 | | 5(2x+7)=15x-10 | | 8b-7b=151b= | | 11.1n=n | | X-18=30x | | -3/5x=5/3x+x | | 10(x+1)=5(2x+20) | | 11m=12m+12 | | 90x+257.125x=3537000 | | 60=-5(x+6) | | 20+5c+20=-20-5c | | (3x+9)30=90 | | 6y+8=23 | | -7+6n=6+5n | | 10u+7=-3+3u+5u | | -17p+4=60+(-5) | | H=5+75t-16t^2 | | 7+5g=-9+9g-6g | | 5n+18=4n+18 | | 4.3t-2.1t=2.3=7.6 | | y-⅘=-⅖ |

Equations solver categories